Cruces of Beowulf. - Cox, Betty S. (De Gruyter, 1971)
No detailed description available for "Cruces of Beowulf".
List of Abbreviations; I. Introduction; II. Heaven for Heathens: Old Testament Christianity in Beowulf; III. The Principle of Contrast and its Relation to Cruces of Beowulf; IV. The Gifstol and the Ark; V. The Old English Satan and Grendel's Motive; VI. Idols, a Rhythm, and a Comparison; VII. Old English Polonius; VIII. From Dane to Geat, Comfort to Comfort, Funeral to Funeral; IX. Afterword; X. Bibliography; Index
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Beowulf; Beowulf; Epic poetry, English (Old) -- History and criticism; Monsters in literature; Dragons in literature; Heroes in literature; Poésie épique anglaise (vieil anglais) -- Histoire et critique; Monstres dans la littérature.; Dragons dans la littérature.; Héros dans la littérature.; Dragons in literature; Epic poetry, English (Old); Heroes in literature; Monsters in literature; Criticism, interpretation, etc